2021
DOI: 10.17576/jsm-2021-5010-20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Relationships between Corneal Parameters, Ocular Biometry, and Myopia Magnitude

Abstract: Axial length of the eye correlates with the magnitude of myopia. However, there are conflicting reports on the relationship between certain corneal parameters with myopia magnitude. The objective of this study was to compare ocular biometry and corneal parameters between emmetropic and myopic groups. Participants (n=127) were categorized as emmetropia (spherical equivalent, SE, ±0.50D), low myopia (-0.75D≤SE<-6.00D) and high myopia (SE≥-6.00D). The difference in axial length, anterior chamber depth, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As far as we know, studies have only focused on the relationship between CCT and refractive errors, and the relationship between CV and refractive errors was absent until now. Previous studies have reported that CCT was not significantly associated with refractive errors 20,21 and demonstrated that CCT was highly inherited 22 . Heritability studies conducted in twins and family members indicated that CCT is one of the most highly heritable human traits 23,24 .…”
Section: Discussionmentioning
confidence: 94%
“…As far as we know, studies have only focused on the relationship between CCT and refractive errors, and the relationship between CV and refractive errors was absent until now. Previous studies have reported that CCT was not significantly associated with refractive errors 20,21 and demonstrated that CCT was highly inherited 22 . Heritability studies conducted in twins and family members indicated that CCT is one of the most highly heritable human traits 23,24 .…”
Section: Discussionmentioning
confidence: 94%
“…A recent study by Hairol et al . [ 16 ] reported that corneal curvature correlated significantly with axial length (P=0.001) but not with myopia magnitude (P=0.91). They concluded that myopia magnitude and axial length are more sensitive to detecting changes in corneal curvature in myopes.…”
Section: Introductionmentioning
confidence: 99%